Desain Perangkat Visual Voice Recording pada Praktikum Aerodrome Control Tower di Politeknik Penerbangan Makassar - Sukarman; Djunaedi; Ucok; Sabur, Fatmawati (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
Vocational education, especially Air Traffic Controller personnel with 70% practicum. Currently there are no VIVO facilities available for recording practicum implementation which can be utilized by cadets to assist the learning process outside of practicum hours/especially in ADC practicum activities. The aim of the research is to design a VIVO recording device for ADC practicum activities. The research uses the R&D method by adapting the ADDIE model. The research sample was 24 MLLU study program cadets. The research instrument used the Gutman scale. The device testing instrument is the black box test. Data analysis techniques use Excel data processing. The obtained by analysis based on device needs were 83% stating that the ADC practicum learning process required supporting tools in the independent learning process in the dormitory, 91.7% needed interactive learning facilities and 95.8% needed learning experiences. The design of the visual sound recording device utilizes a CCTV device that can be accessed anywhere 24 hours via an Android mobile device. feasibility test using the black box test method by paying attention to the features of the ezviz device and the process of setting up the CCTV device, while the implementation stage of the vivo device was carried out at the 9th to 14th meetings.